PELATIHAN PENGGUNAAN VIDEO CONFERENCE MENGGUNAKAN GOOGLE MEET UNTUK SISWA DI DESA PAGERAGUNG KECAMATAN WALANTAKA KABUPATEN SERANG - Firdaus Firdaus (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
This training activity on the use of video conferencing using Google Meet aims to introduce interactive online learning media to students. The choice of video conference in the form of Google Meet is because this application is very light in terms of storage capacity and all features can be used for free. The method used is in the form of workshops that are carried out offline while still complying with the covid 19 health protocol. Steps start from preparation in students and training locations and implementation is carried out starting from guiding the installation process of the google meet application to introducing the available features. The training carried out received a good response from students because after the training they felt that the Google Meet application could later be used not only for learning but also to stay in touch with friends and family.